Independence from the perspective of the Shari'ah committee - Nor Hafizah Zainal Abidin; Fatimah Mat Yasin; Ahmad Zainal Abidin (Asian Journal of Accounting Research, 2020)
The purpose of this study is to gather the perceptions of the Shari'ah committee members on what and how they safeguard and strengthen their independence in fact and independence in appearance during the discharge of their duties.Data were gathered through semi-structured interviews with 13 Shari'ah committee members from 13 different Islamic financial institutions (IFIs).Based on the Islamic worldview and agency theory, the findings suggest that safeguard measures within the context of the Shari'ah committee are strengthened by the following factors: presence of competencies, personal characteristics of the Shari'ah committee members, board engagement, role of the chairman in the Shari'ah committee and accountability to God. Based on the agency theory, it can be suggested that the characteristics of the Shari'ah committee and the presence of an effective governance structure are able to minimise threats to the independence of the Shari'ah committee and enhance its effectiveness.The insights from this study highlight that proper and fit criteria need to be enhanced to ensure the independence of the Shari'ah committee members when performing their roles for IFIs. Moreover, it shows that board engagement and chairman involvement in overseeing the Shari'ah committee in the discharge of its duties is able to improve the independence of the Shari'ah committee both in fact and in appearance.This study contributes to the evidence on safeguard measures in the Malaysian context, which is highly regulated in relation to the Shari'ah governance practices in IFIs. This evidence could be considered by other Shari'ah committees in different contexts.